KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MATERI FUNGSI EKSPONENSIAL KELAS X SMA - Febriana, Nina; Mairing, Jackson Pasini; Sugiharto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2023)
This study aims to describe students' mathematical communication abilities in writing and orally and to find out the factors causing the low mathematical communication skills of students in one of the Palangka Raya High Schools. This research is a qualitative descriptive study. This research was conducted in the odd semester of the 2022/2023 academic year. The subjects of this study were students of class X-MIPA 4 at the school. To find out the factors causing the low ability of students' mathematical communication, 2 students were selected from each category of students' ability to be interviewed. Data collection techniques using written and oral tests and interviews. The results showed that students' mathematical communication abilities in the exponential function material in this class were moderate. Internal factors that cause low students' mathematical communication skills are: 1) Knowledge: Students cannot explain exponential functions, 2) Understanding: Lack of students' ability to understand the intent of the questions and content of the material so that students cannot solve the questions given, 3) Application: lack of students' ability to apply formulas related to exponential functions.